Pengaruh Ekstrak Daun Cengkeh (Syzygium aromaticum L.) sebagai Repellent terhadap Jumlah Lalat yang Hinggap selama Proses Penjemuran Ikan Asin di Senggarang Tahun 2019 - Indra Martias; Nur Ajadit (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2020)
The content of clove leaves (Syzygium aromaticum L.) which gives rise to the distinctive aroma is a component of essential oils. Repellent use generally does not directly kill insects, but rather serves to resist the presence of insects, mainly due to the pungent odor. The purpose of this study was to determine the effect of using clove leaf extract (Syzygium aromaticum L.) as a repellent when drying salted fish in Sengarang. This experimental research uses after only design. Effect of clove leaf extract as a natural bioinsecticide with concentrations of 15%, 30%, and 60% with once repetition. Analysis using univariate and bivariate analysis, then tested with the One Way Annova statistical test. The results showed the average flies at 15% concentrations were 36 heads, 30% were 4 flies and 60% concentrations were 1 flies. The concentration of clove leaf extract (Syzygium aromaticum L.) which is the most effective as repellent flies when drying salted fish is a concentration of 60%. This research can provide information about alternatef fly repellent when drying salted fish by using natural ingredients namely the use of clove leaf extract (Syzygium aromaticum L.). Next researchers need to take measurements of the density of flies every hour when observing.